Lokalitas Kitab Tafsīr al-Ibrīz Karya KH. Bisri Mustofa - Fahmi, Izzul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2019)
The treasury of Qur’anic interpretation in Indonesia, from the early generation of its emergence to the present generation, has been always a relevant object of research to discuss. This is because the works of tafsīr in Indonesia possess their own characters, which differ from that of the similar work in other places. It can be found, among others, in the work of Tafsir al-Ibrīz written by Bisri Mustofa in 1960. This work possesses a distinctive characteristic of Nusantara such as the use of Javanese language as its main presentation language and the use of Arabic-Pegon letter. Another distinctive feature is the element of Javanese-Indonesian local wisdom contained in the work. This article will examine the background of the preparation of this work and the extent of its locality. The writing of al-Ibrīz, instead of a means of worship and seeking God’s pleasure, can also be seen as an attempt to “promote” the local wisdom of Islam Nusantara which is reflected, among others, in the culture of Javanese mysticism, the pilgrimage of awliyā’ tombs, and the Javanese ancestor’s potion.